Prevalence of Oral Mucosal Lesions in Geriatric Patients in Universitas Airlangga Dental Hospital - Fatma Yasmin Mahdani, - (University of the Philippines Manila, 2019)
Background. Population aged 60 years old and above are growing in number; a fact that will have an impact on general and oral health in the future. Oral health is often overlooked in the management of geriatric patients but it is vital to have a knowledged-based practice in order to increase the quality of life of elderly patients. Objective. The purpose of this study is to determine the number and types of oral mucosal lesions in geriatric patients who come to the Universitas Airlangga Dental Hospital. Methods. This is an observational descriptive study with cross-sectional design. Intraoral soft tissue examination was performed on geriatric patients coming to the hospital between March and December 2018. Results. One hundred twenty-four (124) new geriatric patients came to the hospital. A total of 152 oral lesions from 63 geriatric patients (50.81%) were identified. Overall, coated tongue (55.56%) was the most frequently detected lesion, followed by linea alba buccalis (31.74%) and lingual varicosities (26.98%). Conclusion. Coated tongue or white tongue is the most frequently detected oral mucosal lesion, often caused by poor oral hygiene. The dentist should be able to recognize and differentiate them from the worrisome lesions and decide on the appropriate treatment in geriatric patients.